2015
DOI: 10.1016/j.ajpath.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

ADAR1 Prevents Liver Injury from Inflammation and Suppresses Interferon Production in Hepatocytes

Abstract: Adenosine deaminase acting on RNA 1 (ADAR1) is an essential protein for embryonic liver development. ADAR1 loss is embryonically lethal because of severe liver damage. Although ADAR1 is required in adult livers to prevent liver cell death, as demonstrated by liver-specific conditional knockout (Alb-ADAR1 KO ) mice, the mechanism remains elusive. We systematically analyzed Alb-ADAR1 KO mice for liver damage. Differentiation genes and inflammatory pathways were examined in hepatic tissues from Alb-ADAR1 KO and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 75 publications
0
36
0
Order By: Relevance
“…During the preparation of this manuscript, Wang et al 35 reported their findings in a similar model of hepatocyte specific ADAR1 KO. In agreement with our observations, they also show that Adar deletion in hepatocyte caused significant liver injury and alterations in synthetic liver functions coupled with increased mortality and severe growth defects of mutant mice.…”
Section: Discussionmentioning
confidence: 96%
“…During the preparation of this manuscript, Wang et al 35 reported their findings in a similar model of hepatocyte specific ADAR1 KO. In agreement with our observations, they also show that Adar deletion in hepatocyte caused significant liver injury and alterations in synthetic liver functions coupled with increased mortality and severe growth defects of mutant mice.…”
Section: Discussionmentioning
confidence: 96%
“…Adenosine deaminase acting on RNA 1 (ADAR1) is a RNA-binding/editing protein and plays an anti-inflammatory role by suppressing cytosolic innate immune sensing of dsRNA by RLRs. ADAR1 has been found to be essential in maintaining liver homeostasis by preventing hepatocyte inflammation and cell death 36 . In liver IRI, ADAR1 expression was induced.…”
Section: Innate Immune Activationmentioning
confidence: 99%
“…IFN-I also has important effects on lethality in diverse models of sepsis or endotoxic shock (8). In addition, numerous studies have suggested that excessive IFN-I signaling could be involved in impairing normal organismal homoeostasis, including the maintenance of both fetal and adult hematopoietic stem cells (9), intestinal homoeostasis (10), and liver morphological and functional integrity (11).…”
mentioning
confidence: 99%